Malaysian pharmacy students’ intention to provide smoking cessation counseling - Simansalam, Saraswathi; Shamsudin, Siti Hadijah; Nik Mohamed, Mohamad Haniki (Elsevier Inc., 2017)
Background and purpose Malaysian National Quit Smoking Program had proposed to integrate smoking cessation counseling skills into all relevant healthcare curricula as one of its strategies to increase the number of Malaysians giving up smoking. More effective implementation of the curricula can be facilitated by further understanding the factors influencing students’ intention in terms of providing smoking cessation counseling. This study, guided by Integrated Behavior Model (IBM), aimed to explore the factors which influenced pharmacy undergraduates in providing smoking cessation counseling. Educational activity and setting Following the elicitation study, the IBM-guided questionnaire was developed and distributed to students from two pharmacy schools which agreed to participate, each representing public and private institutions. Findings A total of 387 pharmacy students participated yielding a 83% response rate. Multiple regression analysis revealed that all three, namely, attitude (23%), perceived norm (16%), and personal agency (16%) were significant predictors of students’ intention. Further analysis revealed ‘experiential attitude’ a component of attitude as the strongest predictor. In other words, students who felt more comfortable had higher intention to provide smoking cessation counseling. Summary An implication of this study is that tobacco-related curricula with an emphasis to enhance students’ comfort level in providing counseling would be of value for these future pharmacists in terms of their intention as well as actual provision of smoking cessation counseling through the mediation of “experiential attitude” and personal agency.